Effects of haemolysis, icterus and lipaemia on coagulation tests as performed on Stago STA‐Compact‐Max analyser. (16th June 2016) - Woolley, A.; Golmard, J.‐L.; Kitchen, S.
Summary: Introduction: Haemolysis, icterus and lipaemia (HIL) may affect haemostasis test results. This may be influenced by the level of interfering substance and the reagents and end‐point detection system used. Methods: We assessed the influence of HIL on prothrombin time, activated partial thromboplastin time and fibrinogen assay using a viscosity‐based detection analyser. Results: Spontaneous haemolysis that occurred during sample collection and processing had no effect on PT with either a rabbit tissue factor extract or recombinant human tissue factor reagents. In contrast, addition of mechanically haemolysed cells impacted on PT for the highest haemoglobin concentration. For APTTs determined with STA®‐Cephascreen® reagent, there was no significant difference between results in haemolysed and nonhaemolysed samples. For the other two reagents studied, APTTs were statistically significantly shorter in haemolysed samples compared with nonhaemolysed samples. This bias was clinically significant only for STA®‐PTT Automate. For all three APTT reagents, the impact of haemolysis was sufficient to impact patient management decisions, and in some samples, the effects of lipaemia and icterus were not clinically significant. Conclusion: Overall, our results confirm that PT and fibrinogen were not clinically significantly affected by HIL. The APTTs of some haemolysed samples were falsely normal. Haemolysed samples for APTT determination should be rejected.